Analysis of a Tall Structure Considering Glass Panels at Exterior Under Wind Load Using Staad.Pro - Singhai, Yogesh Rohit; Singhai, Murlidhar Chourasiya (International Journal of Scientific Research in Civil Engineering, 2024)
Glass buildings have emerged as a popular architectural style, reshaping our perceptions of space, light, and interaction with the environment. This abstract investigates the transformative potential of this approach, specifically its impact on aesthetics, sustainability, and human experience. In this study, we are investigating toughness and resistance of Glass building with G+11, a 12-story building and a typical storey height of 3.5m and a basic wind speed of 44 mph. STAAD.Pro V8i SS6 Software is used to conduct the research. Toughness describes a material's ability to withstand stress and strain without breaking or deforming significantly. In the case of glass buildings, this refers to their ability to withstand environmental stresses such as wind, earthquakes, and temperature fluctuations and the resistance of glass is a measure of how resistant it is to the flow of electric current. The resistance of glass is determined by a variety of factors, including its type, thickness, and surface properties.
Keywords: Glass Structure; Transparent building; Sustainable Building; Environment Friendly Structure; Wind Analysis; Staad pro